A coexistência como resistência: um esboço na definição de coletivo a partir das práticas artísticas de três grupos em Fortaleza, Ce - Hissa, Celina Cavalcante (2015)
This dissertation investigates the concept of collective from an investigation into the actions of three artistic groups in Fortaleza in the first decade of the twentieth century , they are: Transição Listrada, Balbucio and Alumbramento. Founded on the assumption that the collective to overflowing for the works , the dissertation is not limited to investigating the works alone and accepts the invitation to analyze the processes that give rise to . The concept of equality (RANCIÈRE), political friendship (AGAMBEN) and action (ARENDT), guide our thesis that understands the collective as something of the political order, of action and of co-existence and therefore as a resistance so the current system.